Application of phytoplankton community structure for ranking the major riverine catchments influencing the pollution status of a lake basin. Issue 1 (18th February 2020) - Aura, Christopher Mulanda; Odoli, Cyprian; Nyamweya, Chrisphine S.; Njiru, James M.; Musa, Safina; Miruka, Jared Babu; Owili, Monica Ochieng; Omondi, Reuben; Raburu, Phillip; Manyala, Julius; Mwamburi, Job; Ogari, Zachary; et al.
Abstract: The present study demonstrates the application of a multi‐metric Phytoplankton Index of Biotic Integrity (PIBI) approach for ranking of major river catchments in the Kenyan part of Lake Victoria on the basis of their pollution status. The index utilizes water quality and zooplankton data, phytoplankton diversity, abundance and attributes, as well as literature information. The rivers were sampled from 2016 to 2018 during the wet season (March) and dry season (July). The separation power of the Mann–Whitney U test ( p < .05) qualified eight discriminant metrics for phytoplankton samples into a scoring system of 1, 3 and 5, based on high, fair and slight deviation from the best site, respectively, in development of the final PIBI. The Kuja and Sondu‐Miriu rivers had the highest PIBI, signifying least pollution influence on the lake. In contrast, the Yala and Nzoia rivers exhibited the lowest PIBI, representing the catchments with a higher pollution influence on the lake. The fair to poor integrity classes for the major river catchments in the region signified a deteriorating lakescape. The present study presents the preliminary results of using phytoplankton metrics for development of the Index of Biotic Integrity (IBI) approach in the region as a decision‐making support tool for the effective management and sustainable use of water resources in the lake basin.